Aesthetic reanatomization of smile with support of elastic separators: case report (Research, Society and Development, 2020)
The difference in size, variations in shape as well as the permanence of diastemas in the anterior teeth in adult patients promote changes that often stand out on the face negatively. The aim of this study is to present a clinical case report which diastemas were reanatomized using a direct restorative technique and elastic band, with previous tooth whitening. A 37-year-old female patient attended the Polyclinic School of Faculdade Patos de Minas (FPM) upset with her smile due the color and the spaces between her teeth. The treatment might depend the patient's aesthetics, socioeconomic condition, masticatory functionality, available and the professional's ability to perform the task. Tooth whitening was proposed to resolve the complaint regarding tooth color. Subsequently, for a better proportion of size between the central incisors, movement was performed with orthodontic elastics for better distribution of the diastemas between the central ones. A nanohybrid composite resin was used. This method offers, in addition to the lower cost, the reversibility, the possibility of repair and less time in the execution for not presenting the laboratory stage. Thus, the treatment was well accepted and was able to provide satisfaction to the patient, as it contributed to the improvement of her self-esteem and social acceptance.